Early Detection of Renal Dysfunction in Adolescents Aged 10-13 Years Born with very Low Birth Weight - Yael, Borovitz; Roi, Tschernichovsky; Nir, Sokolover; Esti, Davidovich; Miriam, Davidovits (Archives of Clinical and Biomedical Research, 2020)
Objective: Very low birth weight (VLBW), defined as less than 1500 gr, is an established risk factor for kidney disease in adulthood. To assess that, we examined whether VLBW manifests signs of renal dysfunction at as early as age 10 years, as reflected by elevated blood pressure, proteinuria and reduced glomerular filtration rate (GFR). Methods: 103 children aged 10-13 years and born with VLBW underwent consecutive blood pressure measurements, spot urine analysis, and weight and height measurements. Prevalence rates of hypertension, pre-hypertension and proteinuria were calculated. Characteristics were compared between children with normal and abnormal renal function, to identify risk factors for renal dysfunction. Results: The prevalence of systolic hypertension was 15.8% (95% CI 8.69% - 22.91%) of systolic pre-hypertension 6.9% (95% CI1.96% - 11.84%), and of proteinuria 15.7% (95% CI 8.64% - 22.76%) of the study population. Hypertension was associated with a significantly diminished mean birth weight compared to the remainder of the cohort (939.3gr vs 1111gr, P=0.024). Proteinuria and microalbuminuria were associated with lower mean current body weights: 27.2kg vs 36.7kg P=0.015 and 31.3 kg vs 36.8kg; P=0.023; and with increased mean estimated GFR (126.1 vs 108.3 mL/min per 1.73 m2; P = 0.0059). Conclusions: In a cohort of children aged 10-13 years, who were born preterm with VLBW, disturbed kidney function presented in considerably higher proportions than in general populations of this age. The findings merit considering initiation of routine screening during early adolescence, for hypertension, proteinuria and GFR in this risk group.